Can serum prolactin be a reliable marker for preeclampsia? A hospital based study on Nepalese mothers - Timalsina, S; Gyawali, P (Journal of Chitwan Medical College, 2015)
Preeclampsia is a pregnancy specific complication characterized by hypertension, proteinuria and oedema. It has remained as a major cause of maternal and perinatal morbidity and mortality worldwide. The major function of prolactin is its role in lactation during pregnancy, but many authors have claimed that this hormone is also involved in angiogenesis, thus linking it with the pathogenesis of preeclampsia. In this context, our study aims to compare the serum prolactin level between preeclamptic and healthy pregnancies and correlate with the severity.A total of 54 pregnant women diagnosed with preeclampsia and 60 age and gestational weeks matched healthy pregnant women were recruited in this case control study. Preeclampsia was defined as per Australasian Society Consensus Statement research definition. Among 54 preeclamptic women, 41 had mild preeclampsia and 13 had severe preeclampsia. The mean age and the gestational weeks of the preeclamptic cases and pregnant controls were not significantly different. This study showed that the median concentration of prolactin was significantly higher in preeclampsia than in normal pregnancies (156.6 vs. 129.8 ng/mL, P=0.012). Though the median concentration of prolactin was higher in severe preeclampsia in comparison to mild one, the difference did not reach the significant level (228.3 vs.152.9 ng/mL, P=0.061). No significant correlation of prolactin was found with mean arterial pressure and 24h UTP. Due to poor correlation with established markers of severity, serum prolactin is not a reliable marker of preeclampsia. DOI: http://dx.doi.org/10.3126/jcmc.v5i1.12558